Dynamics of multiple-goal pursuit. [article]. - Louro Maria J.
The authors propose and test a model of multiple-goal pursuit that specifies how individuals allocate effort among multiple goals over time. The model predicts that whether individuals decide to step up effort, coast abandon the current goal, or switch to pursuit another goal is determined jointly by the emotions that flow from prior goal progress and the proximity to future goal attainment, and proximally determined by changes in expectancies about goal attainment. Results from a longitudinal diary study and 2 experiments show that positive and negative goal-related emotions can have diametrically opposing effects on goal directed behavior, depending on the individual's proximity to goal attainment. The findings resolve contrasting predictions about the influence of positive and negative emotions in volitional behavior, critically amend the goal gradient hypothesis, and provide new insights into the dynamics and determinants of multiple-goal pursuit.
Keywords: Multiple goals; Emotions; Effort; Expectancy; Goal gradient